2010
DOI: 10.1002/pola.24396
|View full text |Cite
|
Sign up to set email alerts
|

Alternative initiators for bimolecular photoinitiating systems

Abstract: Typical bimolecular photoinitiators (PIs) for radical polymerization of acrylates show only poor photoreactivity because of the unwanted effect of back electron transfer. Therefore, a PI system consisting of benzaldoxime esters and 4-methyl benzophenone was investigated by photo-differential scanning calorimetry experiments. Surprisingly, reactivities are comparable to that of classical monomolecular Type I PIs like Darocur 1173, probably because of an energy transfer from the triplet state of the benzophenone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 21 publications
0
28
0
Order By: Relevance
“…Therefore, monomers with a lower heat of polymerization per gram than TTA (801 J g À1 ) had to be used and the same experiment was performed in HDDA (650 J g À1 ), which generates significantly less heat during polymerization. [18] All the samples containing the isobutyryl perester P2 could show a propagating polymerization front. Out of the samples with peracrylate PA, 93% polymerized all the way upwards until the monomer was completely consumed, whereas only 60% of the samples of P1 had this ability (see Figure 1).…”
mentioning
confidence: 99%
“…Therefore, monomers with a lower heat of polymerization per gram than TTA (801 J g À1 ) had to be used and the same experiment was performed in HDDA (650 J g À1 ), which generates significantly less heat during polymerization. [18] All the samples containing the isobutyryl perester P2 could show a propagating polymerization front. Out of the samples with peracrylate PA, 93% polymerized all the way upwards until the monomer was completely consumed, whereas only 60% of the samples of P1 had this ability (see Figure 1).…”
mentioning
confidence: 99%
“…Preliminary experiments 19 have indicated that 4-methyl benzophenone A is an efficient sensitizer for 1 . To establish the range of suitable sensitizers, A–C in combination with 1 were tested.…”
Section: Resultsmentioning
confidence: 99%
“…18 Very recently, we have investigated some benzaldoxime esters in combination with 4-methylbenzophenone as sensitizer and have found surprisingly high photoreactivity in photo-DSC experiments. 19 …”
Section: Introductionmentioning
confidence: 99%
“…[19] The nature and the position of electron donor and acceptor substituents are also of primary importance. Of particular interest, the use of ketones, α-diketones or nitro functions [20][21][22] as acceptor groups can not only promote a strong charge delocalization within the π-conjugated structure of the dye but can also induce an efficient intersystem crossing yielding a large amount of reactive excited triplet species. In line with this approach, we have previously demonstrated that the trans-4-propoxy 4'nitrostilbene [23] (PNS in Scheme 1) constitutes a highly reactive 2PA initiator when associated with an aliphatic amine.…”
Section: Introductionmentioning
confidence: 99%